Algebraic Informatics 4th International Conference, CAI 2011, Linz, Austria, June 21-24, 2011. Proceedings - Winkler, Franz (Springer eBooks., 2011)
This book constitutes the refereed proceedings of the 4th International Conference on Algebraic Informatics, CAI 2011, held in Linz, Austria, in June 2011. The 12 revised full papers presented together with 4 invited articles were carefully reviewed and selected from numerous submissions. The papers cover topics such as algebraic semantics on graph and trees, formal power series, syntactic objects, algebraic picture processing, finite and infinite computations, acceptors and transducers for strings, trees, graphs arrays, etc. decision problems, algebraic characterization of logical theories, process algebra, algebraic algorithms, algebraic coding theory, and algebraic aspects of cryptography.